Problems and Costs of the European Union Expansion with Over 27 States - Marina Zaharioaie; Ana-Maria Pascu (CES Working Papers, 2010)
Once on his way to enlargement, the European Union has taken a road of no return. History has shown that all candidate countries have become a point of EU Member States. The question thus is not where you go to the European Union enlargement, but how it will look after the enlargement of the Union politically, economically and socially. The objective of this paper is to analyze potential problems and costs of enlargement beyond the 27 states. Thus, we performed an analysis on the implications of enlargement to the Balkans to Asia Minor and even to the former Soviet bloc countries.
Keywords: 330; EU enlargement candidate countries; potential candidate countries; the Balkans; Turkey